2007
DOI: 10.1016/j.jhsb.2006.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Metacarpal Cascade Lines’; Use in the Diagnosis of Dislocations of the Carpometacarpal Joints

Abstract: Dislocations of the carpometacarpal joints of the ring and little fingers are common and are frequently missed at presentation. We describe a radiographic observation which assists in the confirmation of the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
(17 reference statements)
2
36
0
2
Order By: Relevance
“…In an attempt to minimize the incidence of missed CMC dislocations, we used and recommended a protocol to evaluate CMC joints by obtaining maximum information from the radiograph described by Fisher et al 14 and Hodgson and Shewring. 15 A CT scan may be the preferred imaging method for the complete assessment of these injuries. 7 In our study, the patients who had a suspected CMC dislocation not visible on x-ray were sent for a CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to minimize the incidence of missed CMC dislocations, we used and recommended a protocol to evaluate CMC joints by obtaining maximum information from the radiograph described by Fisher et al 14 and Hodgson and Shewring. 15 A CT scan may be the preferred imaging method for the complete assessment of these injuries. 7 In our study, the patients who had a suspected CMC dislocation not visible on x-ray were sent for a CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Then, metacarpal cascade lines were drawn on a PA radiograph along the central longitudinal axis of each metacarpal. 15 Normally, all lines should intersect at a point 2 cm proximal to the articular surface of the distal radius 15 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Dans notre série on n'a pas noté de cas d'atteinte de la branche profonde du nerf ulnaire. L'évaluation radiologique des lésions repose sur des radiographies standard de face et de profil pour éliminer des luxations carpométacarpiennes associées dont le diagnostic nécessite de rechercher sur le cliché de face une disparition des interlignes, une diminution de la hauteur du carpe médial et une dysharmonie de l'arc de Gilula (ligne épousant la courbure proximale du carpe distal) [15][16][17], et sur le cliché de profil la recherche d'un défaut d'alignement entre les métacarpiens et la seconde rangée du carpe, l'augmentation du diamètre palmodorsal du carpe est souvent masqué par les métacarpiens centraux [18]. Un cliché de trois-quarts, l'avant-bras en pronation de 308, diminue les superpositions articulaires [6,19].…”
Section: Discussionunclassified
“…The 'true' lateral radiograph of the hand was recommended in the past articles [4,7] and Parkinson and Paton suggested that the angle change between the long axis of the second and fifth metacarpal bones should be evaluated in order to elucidate the CMC dislocation [13]. In addition, Hodgson and Shewring suggested to examine the lines superimposed on the central longitudinal axis of the second to fifth metacarpal bones [8]. These lines (metacarpal cascade lines) normally converge to one point of the distal radius using the posterior-anterior Xrays, whereas the line alignment is disturbed in CMC dialocation.…”
Section: Discussionmentioning
confidence: 99%